Beyond dRGT: a new massive gravity theory? - Wittner, Manuel; Könnig, Frank; Amendola, Luca (Arxiv, 2018)
With the realization that dRGT has difficulties to provide dynamical cosmological solutions, the interest of current research in massive gravity has significantly decreased. The reason for that is not least because it is commonly believed that the dRGT theory is the unique way to describe a massive spin-2 field without ghosts. In this work, we argue that dRGT is very likely not unique by deriving a new massive gravity theory and providing indications for the absence of Ostrogradsky instabilities. For the construction of the theory, we use a disformal transformation of the metric tensor in the dRGT action. By analyzing the decoupling limit, we show that the resulting scalar-tensor theory lives inside the class of beyond-Horndeski Lagrangians as long as the transformation of the metric remains purely disformal. This proves the absence of ghosts in this decoupling limit and hints at their absence in the whole theory. Furthermore, we consider a more general case, in which we allow the conformal factor in the disformal transformation to be different from unity, and discuss the absence of ghosts in this decoupling limit.